08.13 Understanding aberrant il-6 mediated cd4+ t-cell signalling in early rheumatoid arthritis. (1st March 2017) - Ridgley, Laura; Anderson, Amy; Skelton, Andrew; Young, David; Isaacs, John; Carmody, Ruaidhrí; Pratt, Arthur
Abstract : Background: Rheumatoid arthritis (RA) is a heterogeneous disease of immune dysregulation. Transcriptional profiling of circulating CD4 + T-cells identified a 12 gene signature which could distinguish untreated early arthritis patients from disease controls. This signature was enriched for STAT-3 target genes whose expression correlated with circulating IL-6 levels. We hypothesise that pre-exposure of naïve CD4 + T-cells to circulating IL-6 mediates STAT-3 activation and subsequent aberrant effector function following T-cell receptor (TCR) stimulation, providing a mechanism of antigen non-specific immune dysfunction in early RA. Materials and methods: Naïve (CD45RA+) and antigen experienced (CD45RA-) CD4 + T-cells from healthy donors were cultured with IL-6 and equimolar concentrations of soluble IL-6R for 3 days to mimic chronic exposure, before being washed thoroughly and stimulated with anti-CD3/anti-CD28 for 6 days. Activation and proliferation were assessed by flow cytometry measuring cell surface markers and CFSE. RNA was extracted from cells at multiple experimental time points and global gene expression profiling undertaken using an Illumina microarray. Results: Aside from downregulation of IL-6β receptor, no change in the activation of naïve CD4 + T-cells following culture with IL-6 was observed. Pre-exposure of naïve CD4 + T-cells to IL-6 and subsequent TCR stimulation enhanced proliferative capacity and cell activation, in a dose-dependent manner. Interestingly, physiological levels of IL-6, mirroring those found in the serum of RA patient's strongly enhanced naïve CD4 + T-cell proliferation. This effect was less pronounced in memory CD4 + T-cells. In addition pre-exposure of CD4 + T-cells to IL-6 resulted in altered cytokine profiles and T-helper cell differentiation. Pre-exposure of healthy control naïve CD4 + T-cells to physiological levels of IL-6 caused significant STAT-3 activated gene induction which mirror genes previously found to distinguish RA patients from disease controls. These genes were less pronounced and unsustained in memory CD4 + T-cells. Conclusions: In the proinflammatory early RA disease state our data imply that pre-exposure of cells to IL-6 causes increased proliferative capacity and activation status as well as differential gene expression, most prominently in naïve CD4 + T-cells. This highlights that cytokine 'pre-priming' during this critical phase may have consequences for naïve CD4 + T-cell effector function impacting the transition to disease chronicity.